1991
DOI: 10.1073/pnas.88.19.8621
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of pheromone biosynthesis in the moth Helicoverpa zea: action of a brain hormone on pheromone glands involves Ca2+ and cAMP as second messengers.

Abstract: Isolated abdomen and pheromone gland bioassays were utilized to determine the physiological action of the pheromone-biosynthesis-activating neuropeptide (PBAN) in the corn earworm moth Helicoverpa (= Heliothis) zea. An isolated pheromone gland bioassay showed that synthetic PBAN was active at 0.02 pmol, with maximal activity occurring at 0.5 pmol and 60 min of incubation. Second-messenger studies demonstrated that extracellular Ca2+ is necessary for PBAN activity on isolated pheromone glands. The Ca2+ ionophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…Neither the molecular nature of the channel activated by PBAN nor the way the PBAN signal is communicated from PBANR to the channel has been determined. Early studies in heliothine species suggested the involvement of RACCs, 9,10) but were unable to differentiate the type of RACC (SOC or DAG-dependent) activated, and given the species differences observed in sex pheromone biosynthetic pathways, may not be applicable to other lepidopterans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither the molecular nature of the channel activated by PBAN nor the way the PBAN signal is communicated from PBANR to the channel has been determined. Early studies in heliothine species suggested the involvement of RACCs, 9,10) but were unable to differentiate the type of RACC (SOC or DAG-dependent) activated, and given the species differences observed in sex pheromone biosynthetic pathways, may not be applicable to other lepidopterans.…”
Section: Discussionmentioning
confidence: 99%
“…4,8) Further studies designed to characterize the PBAN-activated Ca 2þ channel have suggested that, at least in heliothine species, a receptoractivated Ca 2þ channel is involved. 9,10) The mechanism of activation and the molecular nature of the PBANactivated Ca 2þ channel, however, remain to be resolved. While extracellular Ca 2þ is an absolute requirement for pheromonotropic activity, accumulating evidence suggests that the biochemical processes under PBAN control are species-dependent.…”
mentioning
confidence: 99%
“…For most female moths, sex pheromone production is dependent on an influx of extracellular Ca 2ϩ (2,4), presumably via ROCs (5,6). We have recently shown in B. mori that PBAN binding triggers the opening of SOCs (4), suggesting the possible involvement of STIM1 and Orai1; two proteins that have been identified as essential components of SOC pathways (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that regardless of species, pheromonotropic activity is dependent on extracellular Ca 2ϩ (2), suggesting that PBAN signaling is associated with the influx of extracellular Ca 2ϩ ; we directly demonstrated this crucial event in Bombyx mori using fluorescent Ca 2ϩ imaging techniques (4). Early pharmacological studies in heliothine species suggested that PBAN triggers the opening of receptor-operated Ca 2ϩ channels (ROCs) (5,6). The involvement of ROCs was strengthened when the PBAN receptor (PBANR) was identified as a G protein-coupled receptor that could function upstream of Ca 2ϩ influx when heterologously expressed in cultured insect cells (7,8).…”
mentioning
confidence: 99%
“…The first PBANs identified from brain and subesophageal ganglia contain 33 or 34 amino acids, amidated at the C-terminus [5,14,16,24,27]. Despite significant advances over the last decades [4,10], many questions regarding the precise functional roles of PBANs remain. Recent efforts have focused on identification and tissue-specific expression of PBAN receptors.…”
Section: Introductionmentioning
confidence: 99%